Aluminium coagulants efficiency evaluation for natural water clarification - Радовенчик, Вячеслав Михайлович; Глиняна, Софія Володимирівна; Радовенчик, Ярослав Вячеславович; Калініченко, Надія Василівна (Eastern-European Journal of Enterprise Technologies, 2014)
The results of studying the efficiency of coagulants based on aluminum compounds in the process of clarifying bentonite suspensions are given. It was found that in nature bentonite suspensions are precipitated very slowly, and the residual content of the solid phase in the clarified water is at 19mg/dm3 at the initial turbidity of 34 dm3. Processing of bentonite suspension by coagulant solutions based on aluminum compounds allows improving the result, but it cannot be considered satisfactory. Even with the coagulant dose of 50 dm3 (by ion Al3+) the volume of clarified water does not exceed 25 % of the original, and the residual solid phase concentration ranges from 1.6 to 19.2 dm3. The adjustment of pH cannot significantly influence the situation. Neither the amount of clarified water nor residual concentrations of the solid phase are significantly changed. This situation is typical for all investigated coagulants − aluminum chloride, GOHA 2/3, coagulant “Polvak-68”. It is quite evident that for clarifying bentonite suspensions it is necessary to use other coagulants or combine a simultaneous use of the coagulants with flocculants. Applying the methods, which do not use additional chemical agents can be another best way out.